Peripheral blood detection of systemic graft-specific xeno-antibodies following transplantation of human neural progenitor cells into the porcine spinal cord. (February 2018) - Lamanna, Jason J.; Gutierrez, Juanmarco; Espinosa, Jaclyn R.; Wagner, Jacob; Urquia, Lindsey N.; Moreton, Cheryl; Victor Hurtig, C.; Tora, Muhibullah; Kirk, Allan D.; Federici, Thais; Boulis, Nicholas M.
Highlights: Immunologic response to CNS grafts was detected using peripheral blood samples. This is a potential non-invasive screening for CNS stem cell graft rejection. No difference in graft survival was observed with or without tacrolimus. Mixed immune mediators were observed on histology with or without tacrolimus. Abstract: Extensive pre-clinical and clinical studies have searched for therapeutic efficacy of cell-based therapeutics in diseases of the Central Nervous System (CNS) with no other viable options. Allogeneic cells represent the primary source of these therapies and immunosuppressive regimens have been empirically employed based on experience with solid organ transplantation, attempting to avoid immune mediated graft rejection. In this study, we aimed to 1) characterize the host immune response to stem cells transplanted into the CNS and 2) develop a non-invasive method for detecting immune response to transplanted cell grafts. Human neural progenitor cells were transplanted into the spinal cord of 10 Göttingen minipigs, of which 5 received no immunosuppression and 5 received Tacrolimus. Peripheral blood samples were collected longitudinally for flow cytometry cross match studies. Necropsy was performed at day 21 and spinal cord tissue analysis. We observed a transient increase in xeno-reactive antibodies was detected on post-operative day 7 and 14 in pigs that did not receive immunosuppression. This response was not detected in pigs that received Tacrolimus immunosuppression. No difference in graft survival was observed between the groups. Infiltration of numerous immune mediators including granulocytes, T lymphocytes, and activated microglia, and complement deposition were detected. In summary, a systemic immunologic response to stem cell grafts was detected for two weeks after transplantation using peripheral blood. This could be used as a non-invasive biomarker by investigators for detection of immunologic rejection. However, the absence of a detectable response in peripheral blood does not rule out a parenchymal immune response.